Elevated Endothelial Hypoxia-Inducible Factor-1α Contributes to Glomerular Injury and Promotes Hypertensive Chronic Kidney Disease. Issue 1 (July 2015) - Luo, Renna; Zhang, Weiru; Zhao, Cheng; Zhang, Yujin; Wu, Hongyu; Jin, Jianping; Zhang, Wenzheng; Grenz, Almut; Eltzschig, Holger K.; Tao, Lijian; Kellems, Rodney E.; Xia, Yang
Abstract : Hypertensive chronic kidney disease is one of the most prevalent medical conditions with high morbidity and mortality in the United States and worldwide. However, early events initiating the progression to hypertensive chronic kidney disease are poorly understood. We hypothesized that elevated endothelial hypoxia-inducible factor-1α (HIF-1α) is a common early insult triggering initial glomerular injury leading to hypertensive chronic kidney disease. To test our hypothesis, we used an angiotensin II infusion model of hypertensive chronic kidney disease to determine the specific cell type and mechanisms responsible for elevation of HIF-1α and its role in the progression of hypertensive chronic kidney disease. Genetic studies coupled with reverse transcription polymerase chain reaction profiling revealed that elevated endothelial HIF-1α is essential to initiate glomerular injury and progression to renal fibrosis by the transcriptional activation of genes encoding multiple vasoactive proteins. Mechanistically, we found that endothelial HIF-1α gene expression was induced by angiotensin II in a nuclear factor-κB–dependent manner. Finally, we discovered reciprocal positive transcriptional regulation of endothelial Hif-1α and Nf-κb genes is a key driving force for their persistent activation and disease progression. Overall, our findings revealed that the stimulation of HIF-1α gene expression in endothelial cells is detrimental to induce kidney injury, hypertension, and disease progression. Our findings highlight early diagnostic opportunities and therapeutic approaches for hypertensive chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.